Protective Effect of Hydrogen-Rich Saline on Spinal Cord Damage in Rats - Murat Kayabaş; Levent Şahin; Mustafa Makav; Duried Alwazeer; Levent Aras; Serdar Yiğit; Tyler W. LeBaron (MDPI AG, 2023)
The anti-inflammatory and anti-apoptotic effects of molecular hydrogen, delivered as hydrogen-rich saline (HRS), on spinal cord injury was investigated. Four-month-old male Sprague Dawley rats (n = 24) were classified into four groups: (1) control-laminectomy only at T7-T10; (2) spinal injury-dura left intact, Tator and Rivlin clip compression model applied to the spinal cord for 1 min, no treatment given; (3) HRS group-applied intraperitoneally (i.p.) for seven days; and (4) spinal injury-HRS administered i.p. for seven days after laminectomy at T7-T10 level, leaving the dura intact and applying the Tator and Rivlin clip compression model to the spinal cord for 1 min. Levels of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were measured in blood taken at day seven from all groups, and hematoxylin-eosin (H & E) and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) were used to stain the tissue samples. IL-6 and TNF-α levels were significantly lower in the group treated with HRS following the spinal cord injury compared to the group whose spinal cord was damaged. A decrease in apoptosis was also observed. The anti-inflammatory and anti-apoptotic effect of IL-6 may be a clinically useful adjuvant therapy after spinal cord injury.